2017
DOI: 10.3390/su10010072
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of the Future Impacts of Urban Land Use Change on the Natural Environment by SLEUTH and Cluster Analysis

Abstract: Abstract:Changing land use and urban expansion are key drivers of global environmental change, which are inevitable consequences of economic and social development for many cities. Most land use changes have a negative impact on the natural environment, especially due to their effects on surface temperature, runoff and habitat diversity. Due to the limitation of local government funding and expenditure, it is a challenge for developing countries to create strategies for urban sustainability. This study provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…Road-influenced growth encourages urbanized cells to develop along road network, which simulates the impact of existing transportation infrastructure on urban growth. The mentioned four urban growth rules are performed sequentially in each growth cycle and are controlled by five growth coefficients [44], namely dispersion coefficient, breed coefficient, spread coefficient, road gravity coefficient, and slope coefficient. The relationship between the four growth rules and the five coefficients is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Road-influenced growth encourages urbanized cells to develop along road network, which simulates the impact of existing transportation infrastructure on urban growth. The mentioned four urban growth rules are performed sequentially in each growth cycle and are controlled by five growth coefficients [44], namely dispersion coefficient, breed coefficient, spread coefficient, road gravity coefficient, and slope coefficient. The relationship between the four growth rules and the five coefficients is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…More studies have demonstrated that land use changes can affect the suitability of habitat and diversity, water resources, surface runoff and surface temperatures [49]. Of course, UCG can influence surface temperature.…”
Section: The Heat Impactmentioning
confidence: 99%
“…The authors in [5] demonstrate that the urbanization process affects climate at all scales. Several studies have shown strategies to minimize the impact of growth and of urban density on climate using urban planning as a tool to control land usage and coverage, as well as reduce the impact of the urbanization process [6][7][8]16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The relation between the urbanization process and climate is complex.…”
Section: Urban Morphology and Climatementioning
confidence: 99%